Jesuit education system: creators of credible leaders - Mukti Clarence; Lalatendu Kesari Jena (Vilakshan (XIMB Journal of Management))
Purpose – This paper aims to propose that a Jesuit education can create leaders who can respond responsibly to modern challenges. It is observed that there remains a lacuna in education due to various reasons that fail to penetrate the hearts and minds of students who come only to earn their degrees. Today’s education fails to give students experiences whereby they can understand the poor and the oppressed. Here, the Jesuit education system offers a road map of how a bridge can be built, which can tie up the two ends of rigorous academic and social concern. Design/methodology/approach – The emic observation was employed to corroborate the claim. The researcher is a Jesuit himself who has personal experience of the culture of Jesuit education and does research in the seminal field. The co-author is a Jesuit-run business school professor who knows Jesuit ethos, tradition and their apostolic thrust. Findings – Frequently students join the educational institute, with their minds fixed on which school could provide them with a passport for better jobs with better pay and perks. Resentment is seen in their attitude when something is talked about the responsibility of taking care of the people at the margins of society. Social involvement and responsibility are seen as work done only by a social worker and activist. Also, it is witnessed that tokenism is considered as sufficient work done by the privileged classes. Against this backdrop, Jesuit education has various policies and protocols to ensure that those who graduate from their schools become leaders with a blend of human values, academic excellence and social conscience. Originality/value – The underpinning conclusions are to introduce the unique characteristics of the “Jesuit education system”, which gives fresh impetus to renewal, innovation and re-imagination that our academics or industry require during this change of epoch that we experience today, after COVID-19.